The Establishment of the Court of Astana International Financial Center (AIFC) in the Wake of Its Precursors - Alina, Baimoldayeva; Malik , Zia-Ud-Din (Journal of Legal Studies, 2022)
The Astana International Financial Center's Court is a novel conflict determination effort aimed at attracting investors in the same way similar financial centers in the Persian Gulf have done with their courts and arbitration processes. This article contrasts and compares various approaches, focusing on aspects of private international law like jurisdiction, relevant law, and the admission and execution of judgments and arbitral awards. This research finds that the initiative's success, particularly for junior courts, will be determined by its ability to create amicable relationships with the host country's local courts.